Multiplexed Electrochemical Immunosensor for Obesity-related Hormones Using Grafted Graphene-modified Electrodes as Platforms for Antibodies Immobilization. (2017) - Martínez-García, G.; Agüí, L.; Yáñez-Sedeño, P.; Pingarrón, J.M.
Abstract: An electrochemical immunosensor for the simultaneous determination of ghrelin (GHRL) and peptide YY (PYY) using dual screen-printed carbon electrodes modified with reduced graphene oxide (rGO) is presented. Diazonium salt of 4-aminobenzoic acid (4-ABA) was electrochemically grafted on the modified electrodes allowing covalent immobilization of antibodies. After competitive immunoassays using alkaline phosphatase labelled antigens, the affinity reactions were monitored by DPV upon addition of 1-naphthyl phosphate. Calibration plots showed linear current vs. log [hormone] ranges from 10 -3 to 100 ng/mL GHRL, and 10 -4 to10 ng/mL PYY. The usefulness of dual immunosensor was demonstrated by analysis of spiked human serum and saliva.